Redescription of Isotoma grana Lee, Kim & Kim, 1993 and description of a new species of Isotoma Bourlet, 1839 (Collembola: Isotomidae) from Korea - Park, Kyung-Hwa (Zootaxa, 2018)
A new species, Isotoma koreana sp. nov. is described. It is most similar to Isotoma pinnata Börner, 1909, I. riparia (Nicolet, 1842) and I. grana Lee, Kim & Kim, 1993, in possessing a middorsal longitudinal band on body. It can be distinguished in having a thin central stripe on dorsal side of body, the structure of manubrial apical spines and body chaetotaxy. Isotoma grana is redescribed here from type material and compared with related species. An indentification key to the Sino-Japanese species of Isotoma Bourlet is provided.